2004
DOI: 10.1161/01.atv.0000127025.48140.a3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Interleukin-1 Receptor Antagonist Modulates Plaque Composition in Apolipoprotein E–Deficient Mice

Abstract: Objective-Interleukin (IL)-1 plays an important role in atherosclerosis. IL-1 receptor antagonist (IL-1Ra) is an endogenous inhibitor of IL-1. However, the role of IL-1Ra in the development of atherosclerosis is poorly understood. Methods and Results-Mice that lacked IL-1Ra (IL-1RaϪ/Ϫ) were crossed with apolipoprotein E-deficient (EϪ/Ϫ) mice and formation of atherosclerotic lesions was analyzed after 16 weeks or 32 weeks consumption of a normal chow diet. This study focused on the comparison of atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 42 publications
4
83
0
4
Order By: Relevance
“…14,16 Neutrophils and macrophages promote CNV 23,26 -28 ; IL-1Ra has been shown to inhibit macrophage recruitment to the atherosclerotic plaque in a mouse model. 2 We therefore tested the influence of IL-1Ra treatment on neutrophil and macrophage recruitment to the laser-injury site as a possible mechanism of CNV inhibition (Figure 2). Interestingly, IL-1Ra treatment significantly increased the number of Ly6G-positive neutrophils at 10 hours, suggesting a possible IL-1␤-dependent negative feedback in neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,16 Neutrophils and macrophages promote CNV 23,26 -28 ; IL-1Ra has been shown to inhibit macrophage recruitment to the atherosclerotic plaque in a mouse model. 2 We therefore tested the influence of IL-1Ra treatment on neutrophil and macrophage recruitment to the laser-injury site as a possible mechanism of CNV inhibition (Figure 2). Interestingly, IL-1Ra treatment significantly increased the number of Ly6G-positive neutrophils at 10 hours, suggesting a possible IL-1␤-dependent negative feedback in neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…2 It might thereby indirectly influence angiogenesis. To test this hypothesis, we visualized neutrophils and macrophages/microglial cells 10 hours (Figure 2 Figure 2G) and macrophage/microglial cell ( Figure 2J) prevalence were quantified.…”
Section: Il-1ra Inhibits Cnv Independently Of Macrophage Recruitmentmentioning
confidence: 99%
“…2B) (38). Our real-time polymerase chain reaction (RT-PCR) analysis revealed that deletion of IL-1Ra increases the mRNA expression of the adhesion molecules vascular cell adhesion molecule (VCAM)-1 and intercellular adhesion molecule (ICAM)-1 in the aorta, and enhances mRNA levels of monocyte chemoattractant protein (MCP)-1 (38). These changes may contribute to the enhanced accumulation of Mφs in advanced plaques.…”
Section: Il-1ra and Atherogenesismentioning
confidence: 85%
“…These findings suggest that endogenous IL-1Ra may suppress atherosclerosis. To directly answer the question of whether a deficiency of IL-1Ra promotes the development of ath- (38). Following 32 weeks, the differences in lesion size between these mice failed to achieve statistical significance (38).…”
Section: Il-1ra and Atherogenesismentioning
confidence: 99%
See 1 more Smart Citation